Dual-emission carbon dots based ratiometric fluorescent sensor with opposite response for detecting copper (II). (December 2021) - Huang, Gengli; Luo, Xueli; He, Xie; Han, Yong; Zhao, Haiping; Tang, Wenzhi; Yue, Tianli; Li, Zhonghong
Abstract: Herein, carbon dots with intrinsic dual-emission fluorescence (d-CDs) at 360 nm (F360 ) and 530 nm (F530 ) under excitation of 320 nm were prepared by microwave-assisted heat treatment of o -phenylenediamine (OPD). Cu 2+ could be effectively captured by the d-CDs via coordinating with the nitrogen lone pair of –NH2 to form a complex (Cu 2+ -OPD) by electron pair sharing. The complex can efficiently quench the fluorescence of F360 by through-bond energy transfer (TBET) and meanwhile selectively enhance the fluorescence of F530 by inhibiting the occurrence of photoinduced electron transfer (PET). The unique opposite response of the d-CDs toward Cu 2+ could produce a large change to the value of F360 /F530 and thus the d-CDs were utilized to fabricate a ratiometric fluorescent sensor to detect Cu 2+ with a wide linear range of 0.8–55.0 μmol L −1 and a low limit of detection (LOD) of 44.63 nmol L −1 (R 2 = 0.9989). Recoveries of 95.8–102.3% with relative standard deviations (RSD) < 6.7% were achieved in spiked food samples. Moreover, this sensor possessed excellent selectivity and sensitivity for the quantitative determination of Cu 2+, indicating its promising potentials for constructing a reliable and convenient approach for quick pre-warning of Cu 2+ . Highlights: 1. The lone pair in nitrogen groups quenched the fluorescence at 530 nm by PET 2. Cu 2+ coordinate with nitrogen lone pair by electron pair sharing 3. Cu 2+ -NH2 complex inhibited the PET to enhance fluorescence at 530 nm 4. TBET originated from CDs core to Cu 2+ -NH2 complex to quench fluorescence at 360 nm